Bibliometric Analysis of Social Entrepreneurship and Leadership - Sofiyanti, Neneng; Adawiyah, Wiwiek Rabiatul (West Science Journal Economic and Entrepreneurship, 2023)
This research paper presents a bibliometric analysis of social entrepreneurship and leadership literature to identify key themes, trends, and collaborative patterns within the field. The study uses VOSviewer software to visualize co-authorship networks and generate keyword co-occurrence maps. Data was collected from the Scopus database, focusing on publications from 2013 to this year. The results show six distinct clusters of research themes: social justice, corporate social responsibility, social capital, social class, social leadership, and power. Trend analysis shows a steady increase in research outcomes, underscoring the growing importance of social entrepreneurship and leadership in addressing societal challenges. In addition, the authors' collaboration network shows a thriving research community with active cross-disciplinary collaborations. This visualization provides valuable insights for researchers, policymakers, and practitioners, facilitating the identification of influential works, research gaps, and potential areas for collaboration in social entrepreneurship and leadership.